Jimi Hendrix live in Lviv : a novel - Kurkov, Andreĭ (HarperVia, an imprint of HarperCollins Publishers, 2024)
Strange, almost magical, things are afoot in Lviv. Seagulls circle overhead while the passing breeze carries a briny whiff, even though the coast is far away. A ragtag group of aging hippies gather around a mysterious grave in Lychakiv Cemetery. Among them are an ex-KGB officer and the old subversive he once spied upon. Soon, Captain Ryabtsev and Alik Olisevych band together to uncover the source of the city's "anomalies." Meanwhile across Lviv, Taras, a cab driver, ferries kidney-stone patients over cobblestone streets in his ancient Opel Vectra. He's wooing Darka, a woman who works nights at a currency exchange. The young lovers don't know it, but their fate depends on the two lonely old men, relics of a bygone era, who will stop at nothing to save their city--Back cover.